Danshensu inhibits the IL-1β-induced inflammatory response in chondrocytes and osteoarthritis possibly via suppressing NF-κB signaling pathway - Zhixian Xu; Tie Ke; Yongfa Zhang; Licheng Guo; Feng Chen; Wubing He (BMC, 2021)
Abstract Purpose Osteoarthritis (OA) is the most common inflammatory disease associated with pain and cartilage destruction. Interleukin (IL)-1β is widely used to induce inflammatory response in OA models. This study aimed to explore the role of Danshensu (DSS) in IL-1β-induced inflammatory responses in OA. Methods IL-1β was used to induce chondrocyte inflammation. Cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. IL-6, COX-2, TNF-α, and iNOS mRNA levels were detected by qRT-PCR. MMP3, MMP13, ADAMTS4, ADAMTS5, Aggrecan, Collagen, p-IκBα, and p-p65 protein levels were detected by Western blot. An OA mouse model was established by surgical destabilization of the medial meniscus (DMM), and the Osteoarthritis Research Society International (OARSI) score was evaluated by H&E staining. Results DSS did not affect the levels of inflammatory indicators including IL-6, COX-2, TNF-α, iNOS, PEG2, and NO but suppressed COX-2 and iNOS protein expression in IL-1β treated chondrocytes. In addition, DSS downregulated IL-1β-enhanced expression of MMP3, MMP13, ADAMTS4, and ADAMTS5 and upregulated aggrecan and collagen expression. Moreover, DSS significantly inhibited IL-1β-induced phosphorylation of p-IκBα and p-p65 in a dose-dependent manner in chondrocytes, suggesting it plays a role in the NF-κB signaling pathway. Furthermore, DSS significantly reduced DMM-induced cartilage OARSI score in mice, further demonstrating its protective role in OA progression in vivo. Conclusions Our study revealed the protective role of DSS in OA, suggesting that DSS might act as a potential treatment for OA.